Structural vulnerability to the seismic risk of homes in the Chucchun sub-basin - Carhuaz - Rodríguez Anaya, Rosa Deifilia (2019)
The research had as objectives to identify the characteristics of the territory and theindicators that influence the structural vulnerability of the houses to the simian risk .In the methodology, the non-experimental transectional design was applied, using as a tool a questionnaire for the application of surveys to the sample of 343 dwellings; TheAnalysis Hierarchical Process (AHP) was used to determine the level of vulnerabilityof the houses. The findings show that the territory of the Chucchun sub-basin, dueto the characteristics of the lithology, slope and susceptibility or exposure, presentsconditions of high and very high vulnerability; the results of the surveys show that thehouses present conditions of vulnerability and before the occurrence of the seismicrisk, the houses are highly vulnerable